Improving Students’ Creativity through Development of Teaching Material Lampung Local Wisdom Search, Draw, and Make-Based - Marsus Efendi; Alben Ambarita; Pargito (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
The objective of the study was to realize of Lampung local wisdom teaching materials Search, Draw, and Make-based that were feasible and effective to use to improve the creativity of students. The study was conducted at IV.A SDN 2 Gedong Tataan totaling 10 students. The study was a Research and Development (R&D) carried out by referring to the Borg & Gall design model with a simplification of 8 steps. The results of this study were in accordance with the results of the feasibility test for the development of human resource-based Lampung local wisdom teaching materials using material experts reaching a percentage of 78%, media experts reaching a percentage of 76%, linguists reaching a percentage of 79% and the results of effectiveness were proven by pre-test results 64.5% and post test 86.5%. This indicates that the effect of using Lampung local wisdom teaching materials Search, Draw, and Make-based is proven to improve the creativity of students in the aspects of fluency, flexibility, originality, and elaboration.